TEMBAK DI TEMPAT OLEH ANGGOTA DENSUS 88 TERHADAP PELAKU TINDAK PIDANA TERORISME DIKAITKAN DENGAN PERLINDUNGAN HAK ASASI MANUSIA PELAKU - Indra, Mexsasai; ', YURIADI; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Terrorism, including the category of extraordinary crimes, would require extraordinary measures. Thus the birth of terrorism legislation is not separated from the emergence of the pros and cons. Pros and cons occur because of differences in the starting point of looking at terrorism with the issuance of terrorism legislation. On one side of the counter is based on a view of human rights protection actors (Offender oriented), while the other side of the starting point based on a pro-human rights approach to the protection of the victim (victim oriented).Keywords: Setup - Shoot in place - Terrorist